Normative economics : an introduction to microeconomic theory and radical critiques - Stilwell, Frank J.B. (Australia : Pergamon Press, 1975)
Normative Economics: An Introduction to Microeconomic Theory and Radical Critiques seeks to overcome the problem of taking an orthodox approach in economics introducing it in a critical way. The book covers social objectives and functions of economics; the development of a theory of commodity distribution and exchange; the determining factors of different production techniques; the identification and determination of the combination of goods; the effects of locations and places on microeconomics; and the effects of time on microeconomics.
Includes bibliographical footnotes and index.
rpm 21/02/2018
Loans
Keywords: Economics; Microeconomic theory; Microeconomics